SAT0492 Risedronate for Prevention of Steroid Induced Osteoporosis in Rheumatoid Arthritis Pacients. (10th June 2014) - Stoica, S.; Zugravu, G.
Abstract : Background: Corticosteroids are widely used to suppress hyperactive inflammation in rheumatoid arthritis (RA). Bone loss is a serious side effect of this therapy. Risedronate is frequently used fo prevention and treatment for corticosteroid induced osteoporosis. Objectives: The objective of this study is to assess the effects of risedronate for the prevention and treatment of corticosteroid induced osteoporosis. Methods: The study includes 42 RA postmenopausal women aged between 54-62 years which require long-term corticosteroid therapy at >5 mg/day prednisolone daily. All RA patients fulfilled the 1987 American College of Rheumatology (ACR) revised criteria for RA. All patients were interviewed and examined for the gathering of information on disease and treatment history. All patients received risedronate (35 mg/week), elemental calcium (1000mg/day) and vitamin D (800 U/day) for 12 months. Bone mineral density (BMD) (lumbar spine, hip and whole body) and bone turnover markers (urine deoxypyridinoline, serum osteocalcin) were assessed at baseline, month 6 and month 12. Plain radiographs of the thoracic and lumbar spine for fractures were taken at baseline and month 12. Pacients with gastrointestinal disease and neoplasms were excluded. Results: The duration and dose of prednisolone received by the participants was 18.4±20 months. Osteopenia or osteoporosis (T scores <-1.0) of the lumbar spine and the hip occurred in 74% at baseline. The body mass index (BMI) of the participants was 21.9±2.3kg/m 2 . At month 12, a significant gain in BMD at the lumbar spine (+1.3±2.4%; p=0.005) and the hip (+1.1±2.6%; p=0.01) was observed. No new fracture was reported. 4 patients were withdrawn from the study because non-compliance to treatment (N=3) and adverse events – dyspepsia (N=1). Conclusions: Risedronate is effective for preventing and treating bone loss at the lumbar spine and femoral neck after 12 months treatment in RA postmenopausal women receiving long-term glucocorticoids. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5917